The potential of geothermal energy combined with carbon capture and storage in Trinidad and Tobago / Tzar George... [et.al.] - George, Tzar; Alexander, David; Boodlal, Donnie; Maharaj, Rean (2023)
Even without volcanic formations, Trinidad and Tobago can harness geothermal energy from depleted oil reservoirs with the additional benefit of storing Carbon Dioxide (CO2) in them. This paper evaluates the combination of CCS technology with geothermal energy production utilizing CO2 as the working fluid using the EOR 4 depleted oil well in the Forest Reserve Field in South-Western Trinidad. A reservoir model was created using CMG to test the reservoir’s geothermal viability and CO2 storage capacity. CO2 storage was done using hysteresis and solubility in water since it would not be trapped while being returned to the surface for energy production. The base model constructed was optimized for maximum energy production using a CMOST sensitivity analysis varying specific parameters (matrix porosity, matrix permeability, fracture spacing, rock permeability, thermal conductivity, heat capacity).